Revealing the effects of acute exposure of polystyrene nanoplastics on the performance of Anammox granular sludge. (December 2022) - Li, Hanxiang; Xu, Shanshan; Fu, Lu; Chen, Youpeng; Yan, Peng; Guo, Jinsong; Fang, Fang
Abstract: The widespread use of plastic products has led to large amounts of micro/nano plastics in sludge, affecting the performance of biochemical treatment processes. Anammox is a cost-effective biological nitrogen removal process. However, the effect of micro/nano plastic exposure on the nitrogen removal performance and structural stability of Anammox sludge is unclear. In this study, the ability of Anammox granular sludge (AnGS) to cope with nanoplastic exposure was investigated by an acute exposure test, and the related mechanism was revealed. The effect of acute exposure to nanoplastics on the performance of AnGS showed a dose effect. The SAANH 4+ -N and SAANO2 -N decreased by 26.1% and 19.3%, and structural stability reduced 42.9% after acute exposure with 0.5 mg/mL polystyrene nanoplastics (PS-NPs). The elevated oxidative stress increased the dead bacteria, decreasing the nitrogen removal performance of the sludge. The decrease in the structural stability of AnGS was attributed to the decrease in zeta potential and sludge hydrophobicity. The structural research provides a theoretical basis for assessing the effect on the Anammox process. Graphical abstract: Unlabelled Image Highlights: Acute exposure to PS-NPs led to bacterial death and a decreased structural strength of AnGS. Acute exposure to concentrations of PS-NPs significantly increased the level of sludge oxidative stress. Enhancement of electrostatic repulsion and decrease of hydrophobicity of EPS reduced structural strength of AnGS. The compact structure of AnGS could resist the toxic effects of low PS-NPs concentration.